2018
DOI: 10.2147/dddt.s180837
|View full text |Cite
|
Sign up to set email alerts
|

Formononetin induces vasorelaxation in rat thoracic aorta via regulation of the PI3K/PTEN/Akt signaling pathway

Abstract: BackgroundFormononetin (FMN) is an isoflavone that produces arterial vasodilation. However, the underlying molecular mechanisms are unclear.PurposeThe purpose of this study was to explore the vasorelaxant effect and the potential mechanism of FMN in vascular endothelium in isolated rat aorta.MethodsThe thoracic aortas of Sprague Dawley rats were isolated to test the arterial reactivity in the presence of FMN with or without inhibitors. Bioinformatics analyses, including a Bioinformatics Analysis Tool for Molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 42 publications
(43 reference statements)
0
10
0
Order By: Relevance
“…Phosphatase and tensin homolog deleted on chromosome 10 (PTEN) is a regulatory enzyme that dephosphorylates PIP 3 , leading to Akt suppression. Formononetin binds PTEN, preventing the suppression of the PI3K/PTEN/Atk pathway, therefore contributing to vasorelaxation [ 169 ]. In the rat mesenteric arteries, formononetin-mediated relaxation is partly attributed to the upregulation of eNOS, since it is attenuated by ICI 182,780 [ 170 ].…”
Section: Vasorelaxant Effects Of Isoflavones In Vitromentioning
confidence: 99%
“…Phosphatase and tensin homolog deleted on chromosome 10 (PTEN) is a regulatory enzyme that dephosphorylates PIP 3 , leading to Akt suppression. Formononetin binds PTEN, preventing the suppression of the PI3K/PTEN/Atk pathway, therefore contributing to vasorelaxation [ 169 ]. In the rat mesenteric arteries, formononetin-mediated relaxation is partly attributed to the upregulation of eNOS, since it is attenuated by ICI 182,780 [ 170 ].…”
Section: Vasorelaxant Effects Of Isoflavones In Vitromentioning
confidence: 99%
“…Interestingly, isoformononetin, tectorigenin, and cladrin appeared more potent than daidzein in this study. Previous articles showed different potencies of several isoflavones on various arteries [5,7,11,15,16,[19][20][21][22]. Small discrepancies between the aforementioned studies might derive from the use of different animal, breed, or tissue models or may be due to different vasoconstrictors used to precontract the tested arteries.…”
Section: Discussionmentioning
confidence: 99%
“…), Prunus, Pueraria, and Ononis sp. [5][6][7][8]. Isoflavonoid intake in humans is also increasing due to the use of a variety of dairy products, processed food, and food supplements derived from the aforementioned plants [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Formononetin (FMN) is a bioactive isoflavone compound appeared in Chinese medicinal ingredients, such as Astragalus membranaceus . Recent research has found that FMN has multiple pharmacological effects, including anti‐inflammatory, antioxidant, antitumor and vasorelaxant benefits 26‐28 . Several studies have demonstrated the anti‐inflammatory action of FMN.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has found that FMN has multiple pharmacological effects, including anti-inflammatory, antioxidant, antitumor and vasorelaxant benefits. [26][27][28] Several studies have demonstrated the anti-inflammatory action of FMN. One showed that FMN down-regulated TNF-α, IL-6 and IL-1β in a lipopolysaccharide (LPS)-induced zebrafish with lipidomics and targeted transcriptomics.…”
Section: Introductionmentioning
confidence: 99%